In vitro efficacy of plant growth-promoting rhizobacteria isolated from ginger (Zingiber officinale) rhizosphere for biological control of plant pathogens - Jayanti, Ruth Meike; Kristianingrum, Sabrina Ayu; Setiawan, Andree Wijaya (Jurnal Ilmiah Pertanian, 2024)
The excessive use of synthetic chemical pesticides in controlling plant diseases poses significant challenges to sustainable agriculture. As an environmentally friendly alternative, plant growth-promoting rhizobacteria (PGPR) have shown promise by colonizing plant roots and forming symbiotic relationships that enhance plant growth and suppress plant pathogens. Research on the isolation of PGPR from ginger (Zingiber officinale) rhizosphere in Indonesia remains limited, highlighting the need for further exploration to support genetic resource conservation and sustainable agricultural practices. This study aims to evaluate the potential of PGPR isolates from Z. officinale rhizosphere in Semarang, Indonesia, as biological control agents. Isolates were characterized based on morphology, biochemical traits, and their antagonistic activity against fungal pathogens, including Fusarium oxysporum, Colletotrichum sp., and Alternaria sp. A total of 14 isolates were obtained, exhibiting diverse morphological, biochemical, and antagonistic properties. Among them, isolate 235A2 demonstrated the highest potential as a biological control agent, with capabilities including phosphate solubilization, nitrogen fixation, protease enzyme production, and significant inhibition rates of F. oxysporum (13.79%), Colletotrichum sp. (55.56%), and Alternaria sp. (35.61%) in vitro. These findings underscore the potential of PGPR as a sustainable alternative for biological control of plant pathogens, supporting both enhanced plant productivity and environmental conservation.